Genome sequence of Rhizobium leguminosarum bv trifolii strain WSM1689, the microsymbiont of the one flowered clover Trifolium uniflorum - Terpolilli, Jason (Michigan State University, 2013)
Rhizobium leguminosarum bv. trifolii is a soil-inhabiting bacterium that has the capacity to be an effective N(2)-fixing microsymbiont of Trifolium (clover) species. R. leguminosarum bv. trifolii strain WSM1689 is an aerobic, motile, Gram-negative, non-spore-forming rod that was isolated from a root nodule of Trifolium uniflorum collected on the edge of a valley 6 km from Eggares on the Greek Island of Naxos. Although WSM1689 is capable of highly effective N(2)-fixation with T. uniflorum, it is either unable to nodulate or unable to fix N(2) with a wide range of both perennial and annual clovers originating from Europe, North America and Africa. WSM1689 therefore possesses a very narrow host range for effective N(2) fixation and can thus play a valuable role in determining the geographic and phenological barriers to symbiotic performance in the genus Trifolium. Here we describe the features of R. leguminosarum bv. trifolii strain WSM1689, together with the complete genome sequence and its annotation. The 6,903,379 bp genome contains 6,709 protein-coding genes and 89 RNA-only encoding genes. This multipartite genome contains six distinct replicons; a chromosome of size 4,854,518 bp and five plasmids of size 667,306, 518,052, 341,391, 262,704 and 259,408 bp. This rhizobial genome is one of 20 sequenced as part of a DOE Joint Genome Institute 2010 Community Sequencing Program.